Water quality for use in agroecological cultivation of vegetable crops - Cardoso, Ana Carolina Roque; Peixoto, Pedro Gomes; Millan, Rodrigo Ney (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
Several anthropic activities provide wastes and rejects in ecosystems mainly aquatic, and usually inadequately. As a result there can be increases in the amount of nutrients mainly of phosphorus and nitrogen making a medium conducive to Cyanobacteria blooms. The objective of study was identify and quantify the phytoplankton community and water nutrients from June to November 2015 at three points in one branch of Rio Grande, Frutal-MG, to verify the possibility of using water for irrigation of agroecological crops of olerícolas. At the three sampling points the variables temperature, conductivity, dissolved oxygen and pH were in accordance with CONAMA 357/2005. The nutrients (total phosphorus, orthophosphate, nitrate, nitrite and total ammoniacal nitrogen) presented low concentrations and remained in compliance with the resolution in all sites and periods analyzed. The abundance of phytoplankton was divided into 3 large groups: Bacillariophyceae, Chlophyceae and Cyanobacteria. Large amounts of cyanobacteria were observed in the samples, posing a risk due to the potential of these algae to produce toxins. To be used in irrigation of agroecological crops, it is necessary that the water in question goes through treatment.